Public Involvement & Engagement in health inequalities research on COVID-19 pandemic: a case study of CIDACS/FIOCRUZ BAHIA - dos Anjos Fonseca, Adalton; Moraes Pimenta, Denise; Rodrigues Sebastião de Almeida, Mariana; Tourinho Lima, Raiza; Barreto, Mauricio Lima; Travassos Ichihara, Maria Yury (International Journal of Population Data Science, 2023)
Introduction Health inequalities in Brazil have deepened on Covid-19 pandemic, and the most vulnerable people were the more affected. A multidisciplinary team from Cidacs/Fiocruz Bahia developed a Social Disparities Index for Covid-19 (IDS-COVID-19) to support the evaluation of effects of health inequalities on the pandemic in Brazil. Public Involvement and Engagement were the pillars of this research because they allowed us to access first hand experiences about the social context in our country. Objectives This paper aims to describe our Public Involvement and Engagement experience by analysing our challenges, strategies, activities, results, and lessons learned during the construction of IDS-COVID-19. Methods The basis of the IDS-Covid-19 public engagement model was the participation of different social groups through methods and techniques that allow dialogue. Several activities and communication products supported the continuous interactions. Another guideline was the inclusion and the welcoming of participants from the beginning of the project to ensure that the participant's contributions could drive decision-making about the research. Results Participants made several contributions to the research as a new layer of information to the Index, and improvements were made to the interactive panel. They also compromised to support the dissemination and use of the product. Eight representatives of community groups and 29 policymakers participated in our engagement activities during the project. More than 500 people were in our open webinars. In addition, more than 140 news items about IDS-Covid-19 were published in national and international media. Conclusions We highlight as lessons learned the adaptation of some dissemination formats to the public, and the necessity of being flexible and accessible to participants. We strengthened the relationship with relevant stakeholders by exploring individual conversations by phone, WhatsApp, email, and interviews to produce a documentary that registered this whole experience. Cidacs/Fiocruz Bahia has also embedded public engagement and involvement in the study agenda.